Improving social functioning in community-dwelling patients with schizophrenia: a randomized controlled computer cognitive remediation therapy trial with six months follow-up. (May 2020) - Zhu, Xiaolin; Fan, Hongzhen; Fan, Fengmei; Zhao, Yanli; Tan, Yunlong; Yang, Fude; Wang, Zhiren; Xue, Fen; Xiao, Cunli; Li, Wenxiu; Li, Zhiwu; Ma, Liang; et al.
Highlights: CCRT improved social functioning and general cognitive function in community-dwelling patients with schizophrenia. These improvements of social functioning and general cognitive function persisted for 6 months after treatment. CCRT also led to improvements in functioning and symptom severity by modulating cognitive functioning. Abstract: Computerized cognitive remediation therapy (CCRT) has been found to generally improve cognition among patients with schizophrenia, but its effect on functioning has not been extensively studied. This study addressed this gap in the literature by investigating the effect of CCRT and its long-term efficacy among community-dwelling patients with schizophrenia. 157 Chinese patients with schizophrenia were recruited from communities and randomized to CCRT ( n = 78) or treatment as usual (TAU; n = 79) groups for 12 weeks with 4–5 sessions per week. Neurocognition, functioning, and symptoms of participants were assessed at baseline, after treatment, and at the 6 month follow-up. The CCRT group showed significantly greater improvements than the TAU group regarding the MATRICS Consensus Cognitive Battery (MCCB) total score and social cognition score. Significant cognitive benefits for functioning were observed (Personal and Social Performance scale, PSP). Moreover, improvement of the MCCB total score mediated a positive effect on functional capacity (UCSD Performance-based Skills Assessment, UPSA), and mediated decreases in negative symptoms across both groups. CCRT improved social functioning and general cognitive functioning among community-dwelling patients with schizophrenia. These improvements persisted for 6 months after treatment. CCRT also led to improvements in functioning and symptom severity by modulating cognitive functioning.